Aspect-oriented program testing : an annotated bibliography. - Abd Ghani, Abdul Azim; Parizi, Reza Meimandi (Academy Publisher, 2013)
Research in aspect-oriented software testing has resulted in many approaches as reported in literature. A few papers have devoted to literature survey in this field of research. However, the survey only focuses on certain selected topic and particular approaches rather than providing a comprehensive set of references that cover most of the work related to aspect-oriented software testing as a whole. In this case, there is no work yet reported in the literature to tackle this shortage. Therefore, in this paper a collection of 81 references drawn from journals, conference and workshop proceedings, thesis, and technical reports on the subject of testing aspect-oriented software is presented. Each reference is accompanied by a summary of important finding. The aim when selecting the references was to cover as many related articles starting from the first work on the subject in 2002 until the year 2011. For this reason, the bibliography is intended to help the researcher or practitioner, who is relatively new, in gathering information on the subject. The bibliography is organized according to the following sections: general introduction; background on the subject; issues in testing aspect-oriented software; fault models and types; testing coverage criteria; aspect-oriented testing techniques; and automated support for testing aspect-oriented software.